HUBUNGAN DIABETES MELITUS TIPE 2, HIPERKOLESTEROLEMIA, DAN FIBRILASI ATRIUM DENGAN KEJADIAN STROKE - Febrian, Haikal Youris; Setiarini, Rohmania; Utami, Sukandriani; Luh Kadek Trisna Lestari, (Jurnal Medikes (Media Informasi Kesehatan), 2025)
Non-communicable diseases (NCDs), including stroke, are a major health issue in developing countries and a cause of premature death and disability. Stroke disease data in NTB Province increased from 2013 to 2018 with a prevalence of 4.5% to 8%. Stroke risk factors consist of non-modifiable factors such as age, genetics, race or ethnicity, and modifiable factors such as hypertension, diabetes mellitus, smoking behavior, obesity, and heart disease. The study aims to determine the relationship between type 2 diabetes mellitus, hypercholesterolemia, and atrial fibrillation with the incidence of stroke at the NTB Provincial Hospital. This research is an observational analytical quantitative study using a cross-sectional research design. The sampling technique used was simple random sampling with the Slovin's formula. The study sample was patients who had been diagnosed with stroke in the neurology polyclinic at the NTB Provincial Hospital in 2023 through CT scan examination results with an age of 15-80 years, as many as 97 samples. We analyzed the obtained data using the chi-square correlation test. The results showed that of the 97 respondents, most of them experienced non-hemorrhagic stroke as many as 51 people (52.6%). There was a significant relationship between type 2 diabetes mellitus and the incidence of stroke (p = 0.012). There was no significant relationship between hypercholesterolemia and the incidence of stroke (p = 0.216). There was no significant relationship between atrial fibrillation and the incidence of stroke (p = 0.082). Type 2 diabetes mellitus is one of the factors that influences the incidence of stroke at the NTB Provincial Hospital